Literasi Media Digital di Kalangan Mahasiswa: Mengevaluasi Kesadaran Informasi dan Praktik Media Sosial di Universitas Negeri Medan - Jesika Anastasya Sihotang; Desy Verayanti Br Saragih; Ribkah Panjaitan; Mahfuzi Irwan (Didakta Nusantara: Journal of Education and Learning, 2026)
This study aims to analyze the level of digital media literacy among students of Universitas Negeri Medan (UNIMED), particularly in relation to information awareness and social media practices. A quantitative survey design was employed involving 55 active undergraduate students selected through non-probability sampling. Data were collected using a structured questionnaire based on four dimensions of media literacy: information access, information evaluation, digital awareness, and responsible social media use. The instrument was validated through expert judgment and demonstrated acceptable reliability. Data were analyzed using descriptive statistics, including percentages and mean scores. The findings indicate that UNIMED students generally possess a high level of digital media literacy. Students demonstrate strong awareness of the importance of verifying information, understanding the potential risks of misinformation, and utilizing social media responsibly. However, the results also reveal that awareness does not always translate into consistent information verification practices, indicating a gap between digital literacy knowledge and actual online behavior. These findings highlight the importance of strengthening media literacy education within higher education institutions through the integration of critical thinking, information verification, and digital citizenship competencies. This study contributes empirical evidence on university students’ digital media literacy and provides recommendations for developing educational strategies that foster responsible and critical engagement with social media.